Recruitment of Educators: Efforts to Improve the Quality of Education in MTS Negeri 2 Medan - Muhammad Fuad Zaini, Oda Kinata Banurea, Mansur Hidayat Pasaribu (Journal of Education and Teaching Learning, 2020)
This study examines how the recruitment management pattern was carried out by Madrasahs at MTs Negeri 2 as an effort to improve the quality of education, how recruitment is in its implementation, and whether there are obstacles during implementation and the solutions offered by madrasah management. The research method used is descriptive qualitative with a case study technique. The results of the study include the recruitment process which includes the socialization of the announcement of the admission of new educators, administrative selection, written tests, Madrasah interview tests, and school tests (microteaching, school interviews, computer tests, and Al-Qur'an reading and writing tests) carried out accordingly. procedures prepared by the Recruitment Team. Recruitment is carried out following the implementation procedure by prioritizing the main objective of selecting the most qualified educators according to the standards set by MTs Negeri 2 Medan. Supervision of the Recruitment Team carried out by Madrasahs and Heads of MTs Negeri 2 Medan to avoid the possibility of misappropriation or deviation from the Recruitment Team. Meanwhile, for the supervision and evaluation of new educators obtained from the recruitment selection results, they are given time for internships. Internships are carried out to evaluate new educators, see efforts to improve themselves, and see innovations made even to evaluate moral behavior and work behavior during the internship.